Customer satisfaction of Proton car models in Johor Bahru area / Nik Syuhailah Nik Hussin - Nik Hussin, Nik Syuhailah (2002)
A Car as defined by Oxford Dictionary is a motor vehicle with wheels for carrying passengers. Proton Cars arc the Malaysian National Car. manufactured by PROTON with the objective to: a) rationalize the local automotive industry b) spearhead the development of a local component industry and to enhance greater use of local components c) encourage the upgrading of technology, engineering knowledge and technically skill of the country' s workforce d) assist and develop Bumiputra (the indigenous people in Malaysia) participation in the automotive industry. At present, most cars on the road in Malaysia are by proton Cars. PROTON has also tapped penetrated overseas market such as United Kingdom, Singapore, and many Other due to its product design. price affordability as wen as promotional strategies carried out in respective countries. In Malaysia, most people buy Proton Cars because of many factors. For instance "sense of patriotism , affordability and Proton quality. These factors are said to satisfy the need and Wants of the customers. This study Will examine closely on the level Of satisfaction of Proton Car in Johor Bahru 100k 4P'S namely price, Place (after sales service and service center), Promotion (brand name and promotional package) and product quality (additional special feature, reliability and durability). The Study that the level of satisfaction of Proton is average. Thus it is indeed advisable for PROTON to find various means and keep their existing customers satisfied and to attract potential customers into buying Proton Cars and at the same time to remain the competitive with the cars.